2009
DOI: 10.1039/b809169b
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement and elimination of ordered surface layers of crystalline bubble structures due to gas diffusion

Abstract: We describe a hitherto unknown self-organising effect in wet crystalline bubble structures exposed to air. Due to the escape of gas from the bubbles in the top surface layer, bubbles shrink and create space for the bubbles of the lower layers to interpose themselves at the top. This occurs irregularly, but finally a newly ordered bidisperse top layer is formed. This process can be followed for several episodes of elimination of surface layers. The crystalline orientation influences the speed of shrinkage and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The fcc structure is evident, confirming the provisional conclusion of the earlier work. 9 A quantitative analysis of the mCT data was undertaken using the image processing software MAVI. 22 Through the use of filtering routines, it is possible to reduce image noise and structural defectssuch as merged cells-produced during the image step.…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…The fcc structure is evident, confirming the provisional conclusion of the earlier work. 9 A quantitative analysis of the mCT data was undertaken using the image processing software MAVI. 22 Through the use of filtering routines, it is possible to reduce image noise and structural defectssuch as merged cells-produced during the image step.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…Ordering at a 3d wet foam surface was first reported by Bragg and Nye. 6 Van der Net et al, [7][8][9] conducted detailed investigations of the surface structures of ordered samples, and used ray tracing techniques to deduce the structure of the first three to four layers. This, together with viewing of the underside of floating samples, was highly suggestive of extensive crystallisation within the interior, predominantly in the fcc structure.…”
Section: Introductionmentioning
confidence: 99%
“…Monodisperse aqueous foam has been verified to be in an ordered dense packing after gas injection and before its self-organization. [22,23] Although liquid cells of aluminum foam should also be densely and ordered packed just after gas injection if the influence of the rotating needle is not considered, due to drainage previous to solidification it is not easy for the final aluminum foam structure to be ordered. The main difficulty for obtaining ordered aluminum foam is controlling the cell size, size uniformity, and cell shape during preparation.…”
Section: Discussionmentioning
confidence: 99%
“…studies about ordered stackings of monosized bubbles are based on aqueous foams. [21][22][23] Bubbles can anneal to polydisperse or bidisperse states from the monodisperse system via a selforganizing effect. [22,24] It was also demonstrated that the closepacked FCC structure formed by monosized spherical bubbles transforms into a body-centered cubic (BCC) Kelvin structure with tetrakaidecahedron-shaped bubbles as the liquid fraction decreases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation